1975
DOI: 10.1111/j.1600-0560.1975.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Apoptosis: Cell Deletion by Phagocytosis

Abstract: Apoptosis is a process found in many tissues by which devitalized cells are eliminated in an orderly manner. In skin, apoptosis occurs following sunburn, in Bowen's disease and in basal cell carcinoma. Scattered cells are observed in which the cytoplasm has become condensed and dyskeratotic. These dyskeratotic cells are phagocytized, either in toto or in fragments by surrounding keratinocytes. This process involves the condensation, fragmentation, phagocytosis and digestion of individually degenerated cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 15 publications
2
32
0
1
Order By: Relevance
“…In contrast, proteins involved in the response of cells to apoptotic stress, e.g., p53, are frequently found deleted in a large number of cancers (24). Interestingly, caveolin 1 expression has been reported to be absent in variety of tumor types (46). Therefore, it is significant that certain proteins, i.e., p53 and caveolin 1, act as switches that sensitize cells to apoptosis, and it is these proteins, rather than apoptotic effectors, that are most often downregulated during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, proteins involved in the response of cells to apoptotic stress, e.g., p53, are frequently found deleted in a large number of cancers (24). Interestingly, caveolin 1 expression has been reported to be absent in variety of tumor types (46). Therefore, it is significant that certain proteins, i.e., p53 and caveolin 1, act as switches that sensitize cells to apoptosis, and it is these proteins, rather than apoptotic effectors, that are most often downregulated during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis can occur in spite of the presence of these survival signals if the cell is subjected to adverse stimuli such as inflammatory or immunomodulatory agents (e.g., tumor necrosis factor alpha and Fas), microenvironmental cues (e.g., UV irradiation and hyperosmolarity), or anticancer therapies (e.g., gamma irradiation and daunorubicin) (3,26,36,40,42,46,65). Previous studies have suggested that the effects of apoptotic stimuli can deregulate a major survival signaling pathway, the phosphatidylinositol 3-kinase [PI(3)K]/ Akt pathway and that this deregulation is dependent on the generation of the lipid secondary messenger ceramide (59,65).…”
mentioning
confidence: 99%
“…Although there is convincing tnorphological evidence that apoptosis does occur in hutnan epidetinis under physiological and pathological circutnstances (e.g. [53][54][55][56][57], its role and regulation are still obscure.…”
Section: Apoptosis In the Skinmentioning
confidence: 99%
“…The use of the tertn "dyskeratosis"" illustrates the current terminological confusion. Sotnetimes it is used for keratinocytes showing criteria of individual cell death (53,60), more often, however, for preniatute cornification in the viable layers of the epidermis (59. 61).…”
Section: Apoptosis In the Skinmentioning
confidence: 99%
“…SC formation has been regarded as a form of individual cell death of epidermal keratinocytes induced by UVL injury (Olson and Everett 1975;Obata 1982), but the underlying mechanisms of the cell death are not elucidated. Daniels and Johnson (1974) suggested that the lysosomal damages were the primary event.…”
Section: Discussionmentioning
confidence: 99%